2014
DOI: 10.2196/jmir.2982
|View full text |Cite
|
Sign up to set email alerts
|

Mind the Gap: Social Media Engagement by Public Health Researchers

Abstract: BackgroundThe traditional vertical system of sharing information from sources of scientific authority passed down to the public through local health authorities and clinicians risks being made obsolete by emerging technologies that facilitate rapid horizontal information sharing. The rise of Public Health 2.0 requires professional acknowledgment that a new and substantive forum of public discourse about public health exists on social media, such as forums, blogs, Facebook, and Twitter.ObjectiveSome public heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
71
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 19 publications
0
71
0
1
Order By: Relevance
“…Despite the perceived barriers to using social media for communicating research or clinical information, most participants in this study saw a role for social media in obtaining or disseminating research evidence, which is considerably more than reported in previous literature [8]. Social media has several features that enhance its utility for dissemination of research evidence, which may have contributed to this result.…”
Section: Discussionmentioning
confidence: 70%
“…Despite the perceived barriers to using social media for communicating research or clinical information, most participants in this study saw a role for social media in obtaining or disseminating research evidence, which is considerably more than reported in previous literature [8]. Social media has several features that enhance its utility for dissemination of research evidence, which may have contributed to this result.…”
Section: Discussionmentioning
confidence: 70%
“…Our results show that marijuana-related content was commonly shared by those of an African American background and who are relatively popular and active on Instagram; these findings also correspond with our Twitter study about individuals who tweet about marijuana (Cavazos-Rehg et al 2015b). In terms of implications of our findings, there is a growing body of work on how to utilize social media as a tool for health-related research dissemination (Allen et al 2013; Finch et al 2013; Harris et al 2013; Keller et al 2014). In this regard, it may be useful for individuals designing prevention messages about marijuana on social media to consider the typology of individuals who are socially networking about marijuana-related content.…”
Section: Discussionmentioning
confidence: 99%
“…In general, however, these results may indicate that businesses and individuals who create nutrition infographics for Pinterest lack the training to effectively incorporate HBT into social media campaigns. While research elsewhere indicates that health professionals currently use and understand social media in vocational roles only minimally [47,49,50], the creation of accurate nutrition infographics that include HBT by health professionals may allow Pinterest to be used as an effective health promotion tool.…”
Section: Discussionmentioning
confidence: 99%